Autism risk: What do vaccines have to do with - Crawford, Sarah Adelaide (Academic Journal of Pediatrics & Neonatology, 2017)
Keywords: dept.bio; ⚠️ Invalid DOI

The gene book: Explorations in the code of life - Crawford, Sarah Adelaide (Cognella Academic Publishing, 2018)
The Gene Book: Explorations in the Code of Life is designed to introduce undergraduate college students to foundational concepts in genetics. The text provides in-depth coverage of the essential principles of genetics, from Mendel to molecular gene therapy, and reads like a story, guiding readers through each of these areas in an interesting, engaging, and enlightening way.  Milestone scientific discoveries introduce conceptual topics in each of the 10 chapters. The significance of each genetics paradigm is reinforced by the meaningful research context in which it is placed, whether the focus is single gene inheritance of disorders such as PKU and cystic fibrosis, or more complex genetic phenomena. Chromosomes, cell division, and cytogenetic disorders, including Down Syndrome and leukemia, are presented in a riveting historical context. In addition, the principles of molecular genetics are a major focus of this book. Students learn about the double helix, DNA replication, gene expression, mutation, natural selection, genomics, and the tools of molecular DNA analysis.  Approachable and effective, The Gene Book is a highly readable comprehensive text on genetics principles designed to highlight essential concepts that make up their very core. The text is well suited to undergraduate genetics courses and can also be used as a primer for more advanced undergraduate and graduate courses in medial or molecular genetics.Sarah Adelaide Crawford is professor of genetics at Southern Connecticut State University. Dr. Crawford received a Ph.D. from Columbia University College of Physicians and Surgeons, an M.S. degree in biochemistry from Princeton University, and a B.S. degree from Marymount Manhattan College. She is director of the Cancer Biology Research Laboratory and the recently opened the Autism Research Laboratory at the Southern Connecticut State University.
Keywords: dept.bio

Is it time to begin prenatal/neonatal screening for autism risk? - Crawford, Sarah Adelaide (Global Journal of Pediatrics & Neonatal Care, 2019)
Keywords: dept.bio; peer-reviewed